(untitled) (Plant Tissue Culture and Biotechnology, 2023)
Plant regeneration and dedifferentiation are known to be difficult for sugar beet (Beta vulgaris L.) due to its recalcitrant nature. This leads to low transformation efficiency and thus successful application of plant molecular techniques is limited in sugar beet for its genetic enhancement. A prolific regeneration method has been established by modulating several plant growth regulators on the in vitro regeneration of Beta vulgaris var. V6 KWS Serenada. Several types of explants excised from young seedlings of this variety were used for both direct and indirect regeneration of shoots. The highest response towards direct shoot formation and callus induction were obtained from cotyledonary nodes and hypocotyls, respectively. Explants were cultured on MS medium supplemented with different concentrations of BAP, GA3 and 2, 4 -D for callus induction as well as formation of shoots. Hypocotyls responded well for callus induction on MS medium containing 0.1 mg/l BAP + 2.0 mg/l 2, 4-D, while cotyledonary nodes exhibited the highest responses towards shoot formation on MS medium containing 1.0 mg/l BAP and 1.5 mg/l GA3. MS medium containing 2.0 mg/l IBA produced the highest number of roots per shoot. The in vitro raised rooted plantlets were successfully transferred to soil for acclimatization. Plant Tissue Cult. & Biotech. 33(2): 181-188, 2023 (December)